Design of Arts and Cultural Facilities in Serdang Bedagai District with a Neo – Vernacular Architectural Approach - Mutia Salwa; Samsul Bahri (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Miniature Indonesia is the nickname of Serdang Bedagai Regency, where many ethnic groups live in the Land of the Magic of this Traditional Country. There are still many local residents who do not know the culture in the land where they live. Based on existing problems, a view arose to design Arts and Culture Facilities that would house all arts activities and cultural preservation, especially Malay culture, as the forerunner to the establishment of Serdang Bedagai Regency. The theme approach that will be used to design this Arts and Cultural Facility is Neo-Vernacular Architecture. Neo-Vernacular architecture is an architectural concept that incorporates elements of surrounding culture into buildings by applying patterns or motifs typical of the place itself. Apart from that, the use of a neo-vernacular theme is also in line with the building's function, namely as an arts and cultural facility, where the aim of this project is to introduce the surrounding culture to local people and tourists from outside the area.